Outcome after out-of-hospital ventricular fibrillation or pulseless ventricular tachycardia: comparison of before and after the implementation of the 2010 Guidelines in a single centre (Swiss Medical Weekly, 2019)
AIMS OF THE STUDY Improvements to guidelines and efforts to train and equip laypersons and medical professionals are expected to result in improvements in the outcomes of patients experiencing out-of-hospital cardiac arrest (OHCA). This study aimed to evaluate changes in the survival and neurological outcomes of patients before and after the implementation of the 2010 guidelines. METHODS In a retrospective chart review, we analysed the outcomes of 182 patients who suffered bystander-witnessed, out-of-hospital ventricular fibrillation or pulseless ventricular tachycardia of cardiac aetiology. These definitions were based on the Utstein style. Survival at hospital discharge (study period 2006 to 2015), 1-year survival (study period 2011 to 2015), neurological outcome (cerebral performance category [CPC] score) and the corresponding changes over time were evaluated. In addition, the results were compared with results obtained from a systematic review of the literature. RESULTS Of 1423 confirmed OHCAs, 182 fulfilled our inclusion criteria. 91 were treated between 2006 and 2010, and 91 from 2011 to 2015. Thirty-one (34%) survived until hospital discharge in the first time period, 44 (48%) in the second time period (p = 0.071); 26/31 (83%) and 40/44 (91%) respectively had a CPC score of 1–2. Between 2011 and 2015, the 1-year survival rate of the patients discharged from hospital was 36/44 (82%). All of these 36 patients (100%) had a favourable neurological outcome (CPC 1–2). These results were well within the range reported in the literature, although this range is wide (11 to 52% for survival at discharge and 6 to 47% for survival at 1 year). CONCLUSIONS Survival was found to be at the upper range of the results retrieved by the systematic literature review. However, we found no significant improvements over time. The neurological outcomes of the survivors were favourable. The generalisability of this study is limited by its small sample size. To further improve outcomes, more public health measures, such as a functioning chain of survival, are required (e.g. an effective first responder network).